The pathological features of idiopathic interstitial pneumonia‐associated pulmonary adenocarcinomas. Issue 4 (23rd December 2016) - Kojima, Yoko; Okudela, Koji; Matsumura, Mai; Omori, Takahiro; Baba, Tomohisa; Sekine, Akimasa; Woo, Tetsukan; Umeda, Shigeaki; Takemura, Tamiko; Mitsui, Hideaki; Suzuki, Takehisa; Tateishi, Yoko; et al.
Abstract : Aims: To investigate the pathological features of idiopathic interstitial pneumonia (IIP)‐associated pulmonary adenocarcinoma. Methods and results: Surgically resected adenocarcinomas associated with IIP (the IIP group) and adenocarcinomas without IIP (the non‐IIP group) were subjected to analysis. Adenocarcinomas in the IIP group were subdivided into two groups: one group included tumours connected to bronchiolar metaplasia in honeycomb lesions (the H‐IIP group), and the other included tumours unrelated to honeycomb lesions (the NH‐IIP group). Histomorphological appearance and immunohistochemical expression were compared among the H‐IIP group, the NH‐IIP group, and the non‐IIP group. Most of the tumour cells in the H‐IIP group had a tall, columnar shape that showed similar features to proximal bronchial epithelium, whereas tumour cells in the NH‐IIP group and the non‐IIP group had a club‐like shape that showed similar features to respiratory bronchiolar/alveolar epithelium. Adenocarcinomas in the H‐IIP group tended to be negative for thyroid transcription factor‐1 (TTF‐1) and positive for hepatocyte nuclear factor‐4α (HNF‐4α). The frequency of EGFR mutations was significantly lower in adenocarcinomas in the H‐IIP group, although the frequencies of KRAS and ALK mutations did not differ among the three groups. Conclusions: Idiopathic interstitial pneumonia‐associated pulmonary adenocarcinomas, especially those arising from honeycomb lesions, have distinct pathological features.